Microbial community dynamics of Dan'er barley grain during the industrial malting process. (December 2018) - Li, Xiaomin; Cai, Guolin; Wu, Dianhui; Zhang, Ming; Lin, Cai; Lu, Jian
Abstract: The microbes associated with barley grains are known to have either deleterious or beneficial effects on the malting process, thereby affecting the quality of malt and even beer. Dan'er barley is the major cultivar grown in Jiangsu Province in China, malt derived from this cultivar, however, invariably causes filtration problems. To understand the microbial community of Dan'er barley and its probable effects on malt quality and subsequent brewing process, the present study combined culture-dependent methods and culture-independent PCR denaturing gradient gel electrophoresis (PCR-DGGE) strategies. The results showed that as the dominant microbes, bacterial community structure varied considerably during the malting process, while the fungi load increased at the end of malting process, even in the kilning stage. The great abundance of gram-negative bacteria, which can produce exopolysaccharides and form biofilms, may be the main reason for the filtration defects of Dan'er malt. Pathogenic fungi may also have a negative impact on grain germination and malt nutritional value. Several beneficial lactic acid bacteria and fungi strains were also found. These results may contribute to our knowledge of barley grain-associated microbes, and help optimizing the malting process using the Dan'er barley cultivar to get malt product with better quality. Highlights: The microbiota of Dan'er barley and malt were assessed by culturing and PCR-DGGE methods. The large amount of gram negative bacteria may cause filtration problems of Dan'er malt. Existence of pathogenic fungi can negatively affect germination. Potential beneficial LAB and fungi strains were also recovered.